Paroxysmal Nocturnal Hemoglobinuria: An Underestimated Cause of Pediatric Thromboembolism - Christina Griesser; Michael Myskiw; Werner Streif (TH Open, 2020)
Paroxysmal nocturnal hemoglobinuria (PNH) is a chronic disease caused by complement-mediated hemolysis. Clinical symptoms include intravascular hemolysis, nocturnal hemoglobinuria, thromboses, cytopenia, fatigue, abdominal pain, and a strong tendency toward bone marrow failure. It is a rare disease, especially in children, with high mortality rates without appropriate treatment. We here present the case of a 17-year-old girl with unprovoked muscle vein thrombosis. Flow cytometric analysis showed deficiency of glycosyl-phosphatidylinositol-anchored membrane proteins on all three hematopoietic cell lines and confirmed the diagnosis of PNH. Treatment with the monoclonal antibody eculizumab achieved long-term remission. As flow cytometry is normally not part of the routine diagnostics for pediatric thrombosis, awareness is crucial and PNH is important to consider in all children with thrombosis at atypical sites and abnormalities in blood counts with regard to hemolysis and cytopenia.